Features of feeding difficulty in children with Autism Spectrum Disorder. (April 2014) - Marshall, Jeanne; Hill, Rebecca J.; Ziviani, Jenny; Dodrill, Pamela
Abstract: Parents of children with Autism Spectrum Disorders (ASD) commonly report concerns regarding feeding difficulties and poor nutrition. Feeding difficulties, in the form of undesirable mealtime behaviours and/or skill deficits, can cause parental concern and impact on family dynamics. Poor nutrition can have an impact on development and health outcomes. The purpose of this paper was to review recent research regarding feeding difficulties in children with ASD, in order to describe: (1) the most frequently reported undesirable mealtime behaviours and skill deficits; and (2) dietary intake and weight patterns as markers of nutrition. While the ASD population is a somewhat heterogeneous group, this literature review of 44 research studies identified a number of common issues for these children. Restricted dietary variety, food neophobia, food refusal, limiting diet based on texture, and a propensity towards being overweight were frequently reported. Gaining a better understanding of the common features of feeding difficulties experienced by children with ASD will assist in directing intervention studies. Findings from such studies have the potential to enhance developmental and nutritional outcomes for this group. Well-designed longitudinal research would be valuable in monitoring the impact of feeding difficulties for these children as they age.